Fire-catalyzed vegetation shifts in ponderosa pine and Douglas-fir forests of the western United States - Davis, Kimberley T; Higuera, Philip E; Dobrowski, Solomon Z; Parks, Sean A; Abatzoglou, John T; Rother, Monica T; Veblen, Thomas T (Environmental research letters, 2020)
Increased wildfire activity combined with warm and dry post-fire conditions may undermine the mechanisms maintaining forest resilience to wildfires, potentially causing ecosystem transitions, or fire-catalyzed vegetation shifts. Stand-replacing fire is especially likely to catalyze vegetation shifts expected from climate change, by killing mature trees that are less sensitive to climate than juveniles. To understand the vulnerability of forests to fire-catalyzed vegetation shifts it is critical to identify both where fires will burn with stand-replacing severity and where climate conditions limit seedling recruitment. We used an extensive dendrochronological dataset to model the influence of seasonal climate on post-fire recruitment probability for ponderosa pine and Douglas-fir. We applied this model to project annual recruitment probability in the US intermountain west under contemporary and future climate conditions, which we compared to modeled probability of stand-replacing fire. We categorized areas as 'vulnerable to fire-catalyzed vegetation shifts,' if they were likely to burn at stand-replacing severity, if a fire were to occur, and had post-fire climate conditions unsuitable for tree recruitment. Climate suitability for recruitment declined over time in all ecoregions: 21% and 15% of the range of ponderosa pine and Douglas-fir, respectively, had climate conditions unsuitable for recruitment in the 1980s, whereas these values increased to 61% (ponderosa pine) and 34% (Douglas-fir) for the future climate scenario. Less area was vulnerable to fire-catalyzed vegetation shifts, but these values also increased over time, from 6% and 4% of the range of ponderosa pine and Douglas-fir in the 1980s, to 16% (ponderosa pine) and 10% (Douglas-fir) under the future climate scenario. Southern ecoregions had considerably higher vulnerability to fire-catalyzed vegetation shifts than northern ecoregions. Overall, our results suggest that the combination of climate warming and an increase in wildfire activity may substantially impact species distributions through fire-catalyzed vegetation shifts.